Increased susceptibility to pneumonia due to tumour necrosis factor inhibition and prospective immune system rescue via immunotherapy - Ha, Ryan; Keynan, Yoav; Rueda, Zulma Vanessa (Frontiers in Cellular and Infection Microbiology, 2022)
Immunomodulators such as tumour necrosis factor (TNF) inhibitors are used to treat autoimmune conditions by reducing the magnitude of the innate immune response. Dampened innate responses pose an increased risk of new infections by opportunistic pathogens and reactivation of pre-existing latent infections. The alteration in immune response predisposes to increased severity of infections. TNF inhibitors are used to treat autoimmune conditions such as rheumatoid arthritis, juvenile arthritis, psoriatic arthritis, transplant recipients, and inflammatory bowel disease. The efficacies of immunomodulators are shown to be varied, even among those that target the same pathways. Monoclonal antibody-based TNF inhibitors have been shown to induce stronger immunosuppression when compared to their receptor-based counterparts. The variability in activity also translates to differences in risk for infection, moreover, parallel, or sequential use of immunosuppressive drugs and corticosteroids makes it difficult to accurately attribute the risk of infection to a single immunomodulatory drug. Among recipients of TNF inhibitors, Mycobacterium tuberculosis has been shown to be responsible for 12.5-59% of all infections; Pneumocystis jirovecii has been responsible for 20% of all non-viral infections; and Legionella pneumophila infections occur at 13-21 times the rate of the general population. This review will outline the mechanism of immune modulation caused by TNF inhibitors and how they predispose to infection with a focus on Mycobacterium tuberculosis, Legionella pneumophila, and Pneumocystis jirovecii. This review will then explore and evaluate how other immunomodulators and host-directed treatments influence these infections and the severity of the resulting infection to mitigate or treat TNF inhibitor-associated infections alongside antibiotics.